A Review and Proposed Approach to the Neutrophilic Dermatoses of Childhood. Issue 4 (26th February 2015) - Webb, Kate; Hlela, Carol; Jordaan, H. Francois; Suliman, Sara; Scriba, Thomas; Lipsker, Dan; Scott, Chris
Abstract Neutrophilic dermatoses (NDs) are inflammatory skin conditions that are not associated with infection. The classification and clinical approach to these conditions in children is poorly described. This review classifies these conditions into five nosological subtypes: Sweet's syndrome, pyoderma gangrenosum, aseptic pustules, neutrophilic urticarial dermatoses, and Marshall's syndrome. In addition, we review the various secondary diseases that need to be excluded in the clinical management of the NDs of childhood, with a focus on the autoinflammatory conditions that the reader may not be familiar with. We propose a practical clinical approach to these disorders.